2018
DOI: 10.1016/j.celrep.2018.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Limited Regeneration of Adult Salivary Glands after Severe Injury Involves Cellular Plasticity

Abstract: In the adult salivary glands, the origin of replacement and regenerated acinar cells remains unclear. Although many reports describe the identification of stem cells in adult salivary glands, we have shown that differentiated acinar cells can be maintained and regenerated through self-duplication. Here, we have used genetic mouse models to further investigate acinar cell replacement and regeneration during homeostasis and after injury. Under normal conditions or after duct ligation, replacement of duct and aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
133
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 99 publications
(140 citation statements)
references
References 33 publications
4
133
3
Order By: Relevance
“…While most current treatments for salivary gland dysfunction target expansion of residual salivary acinar cells to repair damaged tissue, regenerative therapy with stem cells is a novel and promising therapeutic approach to replace damaged salivary glands (Carpenter and Cotroneo, 2010;Lombaert et al, 2017;Ogawa and Tsuji, 2017). Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands.…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…While most current treatments for salivary gland dysfunction target expansion of residual salivary acinar cells to repair damaged tissue, regenerative therapy with stem cells is a novel and promising therapeutic approach to replace damaged salivary glands (Carpenter and Cotroneo, 2010;Lombaert et al, 2017;Ogawa and Tsuji, 2017). Several studies have identified and characterized subsets of endogenous salivary progenitor cells that can be exploited to promote tissue regeneration (Lombaert et al, 2008;Chibly et al, 2014Chibly et al, , 2018Pringle et al, 2016;Emmerson et al, 2018;Weng et al, 2018). The use of modified fibrin hydrogels (Nam et al, 2019a), layered sheets of isolated salivary gland cells released from thermoresponsive culture dishes (Nam et al, 2019b) and salivary organoid cultures generated from embryonic pluripotent stem cells (Tanaka et al, 2018) have been explored as regenerative therapies for damaged salivary glands.…”
Section: P2 Receptors In Salivary Gland Regenerationmentioning
confidence: 99%
“…Regeneration following irradiation can also occur but is typically partial and depends upon the degree of injury (Weng et al 2018). Multiple mechanisms can limit regenerative ability.…”
Section: Discussionmentioning
confidence: 99%
“…KRT5 and AXIN2 mark distinct subpopulations of duct cells which give rise to additional duct cells but do not develop into acinar cells. However, following irradiation causing extensive damage, both acinar and duct cells contribute to regeneration by producing cells of both lineages (Weng, Aure, Maruyama, & Ovitt, 2018).…”
Section: Cellular Plasticity Contributes To Tissue Regenerationmentioning
confidence: 99%